Hubungan Self-Esteem dengan Fear of Missing Out pada Remaja Pengguna Media Sosial di SMA Negeri 1 Muntilan Kabupaten Magelang - Alya Auni Mahfuzah; Agustin, Rin Widya (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Adolescence is a phase that is prone to experiencing FoMO behavior. FoMO experienced by adolescence has the potential to cause feelings of loss, stress, and feeling distant if they do not know about important events of other individuals or groups. The FoMO experienced by adolescence indicates that their motivational factors are not developed optimally. The motivational factor referred to is self-esteem. Someone who has high self-esteem in general will be more able to be positive in making an assessment of himself.. This research aims to find out the relationship between self-esteem and FoMO in adolescent social media users at SMA N 1 Muntilan, Magelang Regency. The population in this study is 1056 students of SMA N 1 Muntilan. From this population, the research sample was taken using the proportionate stratified random sampling technique of 286 students based on the Isaac and Michael table formula. Data collection was carried out using a modification of the Fear of Missing Out Scale (FoMOS) and the Rosenberg Self-esteem Scale. The data was tested with product moment pearson through the SPSS 25 for windows program. The research results show that there is a significant negative relationship that is in the very weak category between self-esteem and FoMO in social media users at SMA Negeri 1 Muntilan. This means that even though adolescence have good self-esteem, it is not enough to prevent them from FoMO.